Anticancer and apoptotic effects of a polysaccharide extract isolated from Lactarius chrysorrheus Fr. in HepG2 and PANC-1 cell lines - Mutlu, Dogukan; Cakir, Cansel; Ozturk, Mehmet; Arslan, Sevki (Archives of Biological Sciences, 2022)
Paper description: A polysaccharide extract from Lactarius chrysorrheus was isolated. Potential anti-cancer activity of the polysaccharide extract was investigated in different cell lines. The cytotoxic effect of the extract was estimated, with EC 50 values of 296.42 μg/mL for HepG2 and 444.43 μg/mL in PANC-1 cells, and its apoptotic activity. The polysaccharide extract inhibited cell migration and colony formation and upregulated the expression of CASPASE 3 and CASPASE 9 and downregulated BCL-2 and Bcl-xL genes in HepG2 and PANC-1 cells. This study provides insight into the use of polysaccharides of chrysorrheus in the development of novel anticancer agents. Abstract: Mushrooms are widely used in many cultures for nutritional and health benefits. The Lactarius species is found in the Aegean region of Turkey. Lactarius chrysorrheus Fr. is a wild mushroom that contains a milky juice. In this study, we investigated the in vitro cytotoxic potential and apoptotic effect of the polysaccharide extract prepared from L. chrysorrheus by water extraction and alcohol precipitation using the tetrazolium MTT dye assay, annexin V staining, wound healing and colony formation, and qRT-PCR. The molecular weights of three peaks observed in HPLC chromatograms were calculated as 1869.9, 3043.92 and 16821.47 Da. The extract exhibited cytotoxic activity at 72 h, with an IC50 value of 296.42 μg/mL in HepG2 and 444.43 μg/mL in PANC-1 cells; the extract that was tested on the normal HEK293 cell line exhibited no cytotoxicity. Further, L. chrysorrheus upregulated the expression of CASPASE 3 and CASPASE 9 while downregulating B-cell lymphoma 2 (BCL-2) and B-cell lymphoma-extra large (Bcl-xL) genes, and inhibited cell migration and colony formation in HepG2 and PANC-1 cells. This study provides new insight into the use of the polysaccharide from L. chrysorrheus in the development of novel anticancer agents.